2014
DOI: 10.3390/ijerph120100322
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon Residues in Serum Samples of Autopsied Individuals from Tennessee

Abstract: This study reports the concentrations of Polycyclic Aromatic Hydrocarbons (PAHs) in human blood sera samples (n = 650) obtained at autopsy from individuals who died of drug abuse, alcohol toxicity, homicide, suicide and other unknown causes. The analyzed samples from decedents revealed the presence of PAHs of which B(a)P was the most predominant one, followed by benzo(b)fluoranthene and benzo(k)fluoranthene. The other PAHs detected sporadically and measured were benzo(g,h,i)perylene, acenaphthene, anthracene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…BaP was one of the most commonly detected PAHs in post-mortem blood from male and female Caucasians and African Americans (41), which ranged in concentration from 0.6 ng/mL to 10.5 ng/mL. A similar concentration range of 0-3.7 ng/mL was reported by Al-Daghri et al (11); however, Pleil et al (8), reported median and maximum BaP levels of 0.019 and 0.195 ng/mL, respectively, in plasma obtained from a healthy, non-smoking, adult population with no recent history of remarkable exposures.…”
Section: Discussionmentioning
confidence: 99%
“…BaP was one of the most commonly detected PAHs in post-mortem blood from male and female Caucasians and African Americans (41), which ranged in concentration from 0.6 ng/mL to 10.5 ng/mL. A similar concentration range of 0-3.7 ng/mL was reported by Al-Daghri et al (11); however, Pleil et al (8), reported median and maximum BaP levels of 0.019 and 0.195 ng/mL, respectively, in plasma obtained from a healthy, non-smoking, adult population with no recent history of remarkable exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Radioactive‐labelling studies established that inhaled ultrafine carbon particles could then be recovered in the blood . Advances in bioanalytical methods have now revealed that PAHs and their metabolites can be found in the blood of adults, children and neonates, as well as in urine and maternal milk . Thus, subjects of all ages and all types of organs can be exposed to pollutants.…”
Section: Pollutant Levels In the Skinmentioning
confidence: 99%
“…Clinical studies have correlated daily exposure to particulate matter (PM) with increased skin pigmentation spots and wrinkles [8][9][10]. Among the constituents of harmful atmospheric pollution, polycyclic aromatic hydrocarbons (PAHs), a class of organic pollutants in ambient air commonly associated with PM, may enter the human body and bloodstream via inhalation, ingestion, and dermal absorption [11][12][13]. While chronic dermal exposure to PAHs may be associated with premature skin aging, pigmentary disorder, acne, and skin cancer [10,14,15], the exact mechanisms by which PAH pollution harms the skin remain poorly understood and are likely to be complex and multifaceted.…”
Section: Introductionmentioning
confidence: 99%